Tibolone Ameliorates the Lipotoxic Effect of Palmitic Acid in Normal Human Astrocytes - Martin-Jiménez, Cynthia; González, Janneth; Vesga, Diego; Aristizabal, Andrés; Barreto, George E. (Neurotoxicity research, 2020)
Lipotoxicity is a pathological condition resulting from the excessive accumulation of fatty acids, like palmitic acid (PA), within the cell. This pathological phenomenon induces deleterious metabolic changes in cells and is associated with neurodegenerative diseases, dyslipidemia, and obesity. Recent evidence has demonstrated that tibolone, a synthetic steroid, protects cellular damage through various mechanisms; but its underlying actions upon lipotoxic damage are unknown. In this study, we assessed the effects of tibolone administration on normal human astrocytes subject to supraphysiological levels of palmitic acid as a model to induce cytotoxicity. Our results demonstrated that tibolone attenuated lipotoxic damage of PA in normal human astrocytes by reducing PI uptake in 53%, prevented cardiolipin loss by 17%, reduced fragmented/condensed nuclei by 50.81% and attenuated the production of superoxide ions by around 20%. In conclusion, these data suggest that protective effects of tibolone against lipotoxicity may be mediated, in part, through modulation of the different cellular mechanisms of astrocytes.